Enzymatic Activity Determination for Protein Degradation - FERDIANA (NIM 10504079), FANI
Papaya (Carica papaya L.) is a popular plant which has several benefits, such as, a healthy fruit, source of protease. Latex from papaya contains several protease, such as papain and chymopapain. These enzymes can be collected from unripe green papaya. Enzyme was isolated from latex using three methods. The first method is desiccation using desiccator, freeze dryer, and oven which has temperature at 50oC. From this methods, the enzyme activities can be derived as 0,116; 0,361; dan 0,225 unit/mg. For the second method, enzyme isolated using 0-85% ammonium sulfate saturation gave activity of 0,303 unit/mg. And the third method is procession of latex which is resumed from the journal, it is fraccination by using two steps salt precipitation and has the enzyme activity as 0,046 unit/mg. To test the enzyme in protein degradation, 1% (w/w) processed enzyme added into albumin to make peptone and have % rendemen in a row as 4,36; 8,63; 9,78; 10,64; and 0 %. The content of papain enzyme is set using electrophoresis native gel PAGE and SDS PAGE.